Respuesta :

Answer:

y = 0 or y = 1/9

Step-by-step explanation:

2^√y=8^y

Make sure they have the same base

That's

8 = 2³

So

8^y = 2^3y

2^√y = 2^3y

Since the bases are now the same we can compare the exponents

We have

√y = 3y

Remove the square root by squaring both sides

That's

(√y)² = (3y)²

y = 9y²

Move 9y² to the left side of the equation

y - 9y² = 0

Factorize

y(1 - 9y)

y = 0

1 = 9y

Divide both sides by 9

y = 1/9

The answer is y = 0 or y = 1/9 since they both satisfy the equation

Hope this helps you